Classical caesarean section- A time honoured surgery - Rawal, Suniti; Gurung, Geeta; Bista, Kesang D (Nepal Journal of Obstetrics and Gynaecology, 2008)
Classical caesarean section seldom performed worldwide and even at our hospital was carried out in a 37 years old G3 P0+2 at 36+4 weeks with the indications of transverse lie, cervical fibroid, low lying placenta, oligohydramnios with severe IUGR and PIH, complicated with intraoperative post partum hemorrhage (PPH). Though the classical caesarean section (CCS) is almost a forgotten surgery, its importance may be reminded in situations like this when such an intervention becomes imperative and lower segment caesarean section (LSCS) being lesser advantageous. Key words: classical caesarean section, transverse lie, cervical fibroid, low lying placenta doi:10.3126/njog.v3i1.1442 NJOG 2008 May-June; 3(1): 51 - 54